2022
DOI: 10.1002/2211-5463.13395
|View full text |Cite
|
Sign up to set email alerts
|

‘Everyone is trying to outcompete each other’: a qualitative study of medical student attitudes to a novel peer‐assessed undergraduate teamwork module

Abstract: The centrality of teamwork in ensuring the effective functioning of institutions across all sectors is undeniable. However, embedding teamwork into higher education has been hampered due to a range of deeply entrenched practices associated broadly with the foregrounding of knowledge, beliefs about the place of skill training and routines of assessment. As a result, despite an urgent need to address teamwork, little progress has been made with respect to progressing teamwork education. We have designed and eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
2
0
1
Order By: Relevance
“…The present study focused on the dimensions of teamwork, communication and coordination, and self-learning skill that are deemed of paramount importance to college students’ employability ( He, 2019 ). Teamwork is the core to ensure the effective operation of the organization and all departments within the organization ( Watson et al, 2022 ) and is a highly sought-after competence by employers ( Parratt et al, 2016 ). A qualitative study on job developers revealed that soft skills such as communication and coordination were more desirable than job-related technical skills ( Scheef et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The present study focused on the dimensions of teamwork, communication and coordination, and self-learning skill that are deemed of paramount importance to college students’ employability ( He, 2019 ). Teamwork is the core to ensure the effective operation of the organization and all departments within the organization ( Watson et al, 2022 ) and is a highly sought-after competence by employers ( Parratt et al, 2016 ). A qualitative study on job developers revealed that soft skills such as communication and coordination were more desirable than job-related technical skills ( Scheef et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…While we did not directly evaluate student preferences for peer feedback versus expert feedback, other studies have highlighted student reticence to use peer feedback, 23 while others have noted that students have positive perceptions of peer feedback. 24 At our institution, we found that students generally held favorable opinions about the utility of feedback despite the near neutrality of the confidentiality and sensitivity of peer feedback.…”
Section: Discussionmentioning
confidence: 99%
“…Komandinis darbas svarbus užtikrinant sėkmingą organizacijų veiklą ir sklandų jų darbą. Priklausomai nuo konteksto, komandinio darbo apibrėžimai gali būti sutelkti į galutinį komandos gaminamą produktą, įdiegtus procesus arba požiūrių derinį (Watson et al, 2022). Visgi moderniuoju laikotarpiu, ypač pasaulinės koronaviruso pandemijos metu, išpopuliarėjo nuotolinis darbas, tačiau komandinis darbas neišnyko.…”
Section: įVadasunclassified